Modeling geomagnetically induced currents. Issue 1 (31st January 2017) - Boteler, D. H.; Pirjola, R. J.
Abstract: Understanding the geomagnetic hazard to power systems requires the ability to model the geomagnetically induced currents (GIC) produced in a power network. This paper presents the developments in GIC modeling starting with an examination of fundamental questions about where the driving force for GIC is located. Then we outline the two main network modeling approaches that are mathematically equivalent and show an example for a simple circuit. Accurate modeling of the GIC produced during real space weather events requires including the appropriate system characteristics, magnetic source fields, and Earth conductivity structure. It is shown how multiple voltage levels can be included in GIC modeling and how the network configuration affects the GIC values. Magnetic source fields can be included by using "plane wave" or line current models or by using geomagnetic observatory data with an appropriate interpolation scheme. Earth conductivity structure can be represented by 1‐D, 2‐D, or 3‐D models that are used to calculate the transfer function between electric and magnetic fields at the Earth's surface. For 2‐D and 3‐D structures this will involve a tensor impedance function and electric fields that are not necessarily orthogonal to the magnetic field variations. It is now technically possible to include all these features in the modeling of GIC, and various software implementations are being developed to make these features more accessible for use in risk studies. Key Points: GIC modeling can now include geomagnetic disturbance characteristics and Earth conductivity to calculate GIC throughout a power system Inclusion of geomagnetic disturbance characteristics and 3‐D Earth conductivity structure in GIC modeling is often limited by lack of data GIC modeling has a high state of application readiness and is used for hazard assessments and real‐time geomagnetic disturbance management